CLOUD, AI, AND DIGITAL TRANSFORMATION: A WINNING COMBINATION - Surendra Mohan DevaraJ, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the synergistic relationship between cloud computing, artificial intelligence (AI), and digital transformation in driving business innovation and competitive advantage. It examines these technologies' current state and future projections, roles, and combined impact across various industries. The article delves into specific use cases, implementation strategies, and organizations' challenges in adopting these technologies. By presenting a wealth of statistical data and real-world examples, it illustrates how the integration of cloud, AI, and digital transformation is reshaping business models, enhancing operational efficiency, and creating new opportunities for growth and innovation.